Medical leadership: interns’ perception on leadership skills: a qualitative study from Chennai - Sucharitha, Sree T.; Suganya, E.; Arumugam, Balaji; Shirley, P. (International Journal Of Community Medicine And Public Health, 2018)
Background: Medical leadership, an essential skill for the emerging medical graduates has been rarely studied in India. Methods: A formative research was undertaken among 30 interns selected by purposive sampling method. Triangulation of free listing, pile sorting was done to elicit their perception on leadership attributes. This was followed by a semi-structured focus group discussion to elicit the characteristics and solutions to obtain adequate leadership skills. The data was analysed using Visual Anthropac 4.98.1/X software. Results: Interns perceived communication skills, impartiality, patience, honesty, self-discipline, receptive to others opinions, knowledge of medicine, self-confidence, and guiding teams as major characteristics of effective medical leadership. The respondents admitted they were deficient in the understanding of leadership traits as it was not required of them as medical undergraduates. Internship period provided multiple platforms to develop leadership skills such as demonstrating personal qualities, working with others, goal setting and delivering services individually thereby overcoming a training gap during undergraduate period. Interns suggested that structured training on leadership skills and personality development coupled with exposure to challenging clinical environments during the undergraduate period will help them emerge as confident leaders. Conclusions: Medical education reforms should support the inclusion of leadership training in the MBBS curriculum.